COOPERATION AND INTERNATIONALIZATION EXPERIENCE WITHIN HIGHER EDUCATION - Silvina Elías; Silvia Morresi; Ana María Tombolato (European Scientific Journal, ESJ, 2015)
Education has historically developed parallel to socio-technological changes; at present the innovations in information and communication technologies promote a new educational paradigm, where the search for higher education quality, pertinence and internationalization is remarkable On these lines, the creation of university networks of postgraduate studies, students and researchers mobility and the cooperation of Spanish American researchers who work outside the region constitute one of the goals which Ibero American countries aim at achieving during the next decade (OEI, 2010). Within this context, the aim of this paper is to describe an experience of cooperation and internationalization with teachers and postgraduate students mobility which took place in the Departamento de Economía de la Universidad Nacional del Sur (Department of Economics of National University of the South). This experience took place from 2008 to 2011 in the context of the Programa de Centros Asociados para el Fortaleciomiento de Posgrados, Proyecto CAFP (Program of Associate Centers for the Strengthening of Postgraduate Studies, CAFP Project) and the promoting institution was the Departamento de Desemvolvimento, Agricultura e Sociedade and Instituto de Ciencias Humanas e Sociais (CPDA) of the Universidades Federal Rural do Rio de Janeiro and the receiving institution, the Departamento de Economía of UNS (Department of Economics of the National University of the South). Thus, two postgraduate programs were linked: The Program of Pós Graduacáo de Ciencias Sociais em Desemvolvimento, Agricultura e Sociedades del CPDA and the Magister in Agrarian and Rural Management of UNS. Based on the weaknesses of the latter, the proposed objectives were, among others, improving the graduation rate, revising and updating the Course of Studies, widening the research lines and incorporating interdisciplinary approaches.